Evaluation of Surveillance System of Acute Flaccid Paralysis in Azad Jammu & Kashmir: 2011 to 2015 - -Rehman, 1Dr. Syed Nadeem-ur; Hafeez, Dr. Uzma; Ghafoor, Dr. Tamkeen (International Journal of Pathology, 2018)
Background: The last case of wild polio virus transmission occurred in AJ&K in October 2000.This study was conducted to describe the characteristics of patients reported with acute flaccid paralysis and to evaluate the performance of the surveillance system during 2011-2015 using indicators recommended by the World Health Organization.Methods: This retrospective study was conducted at directorate of Expanded Program on Immunization AJ&K during May 2016. Records were reviewed of children aged younger than 15 years with acute flaccid paralysis. Data analysis was performed using Microsoft Excel 2007.Results: During 2011 - 2015, total 213 AFP cases, aged 01 month to 15 years were reported. 55% were boys. Those below 5 years of age accounted for 62% of cases. A neurological cause was identified in 83% of cases, of which the most common was Guillain-Barré syndrome (63%), followed by transverse myelitis (16%). None of the cases were acute poliomyelitis or polio-compatible. Majority of cases were reported by public sector health facilities (93%). All except one of the performance indicators consistently met World Health Organization requirements and thus demonstrated the effectiveness of the acute flaccid paralysis surveillance system. The acute flaccid paralysis reporting rate consistently exceeded 2.0 per 100 000 population below 15 years of age and satisfied World Health Organization requirements, however it is below national average which is 8.8.Conclusion: AFP surveillance meeting WHO recommended standards has help the state of AJ&K in maintaining a polio free status for over fifteen years. High quality AFP surveillance must be sustained to achieve global eradication of polio.